Pengembangan Tool Holder untuk Meningkatkan Kompetensi Mahasiswa pada Pembelajaran Praktik Pemesinan - Surono Surono; Febrianto Amri Ristadi; Nurdjito Nurdjito; Asnawi Asnawi (Department of Mechanical Engineering Education, 2018)
This research aims to: (1) design a tool holder specified for existing machine tools in Machining Workshop at Mechanical Engineering Education of Universitas Negeri Yogyakarta; (2) Assess the feasibility of the developed design. The research used Research and development (R&D) design incorporating ADDIE Model. Data collection were performed using observation, questionnaire, and documentation. Data were analyzed using descriptive quantitative technique. The results are: (1) tool holder design was suited to the needs of the tools in the workshop, which are mill bits, internal turning tool holder, and tap holder; (2) the overall interpretation are